A concept map of death-related anxieties in patients with advanced cancer. Issue 4 (2nd August 2017) - Vehling, Sigrun; Malfitano, Carmine; Shnall, Joanna; Watt, Sarah; Panday, Tania; Chiu, Aubrey; Rydall, Anne; Zimmermann, Camilla; Hales, Sarah; Rodin, Gary; Lo, Christopher
Abstract : Objectives: Fear of death and dying is common in patients with advanced cancer, but can be difficult to address in clinical conversations. We aimed to show that the experience of death anxiety may be deconstructed into a network of specific concerns and to provide a map of their interconnections to aid clinical exploration. Methods: We studied a sample of 382 patients with advanced cancer recruited from outpatient clinics at the Princess Margaret Cancer Centre, Toronto, Canada. Patients completed the 15-item Death and Dying Distress Scale (DADDS). We used item ratings to estimate a regularised partial correlation network of death and dying-related concerns. We calculated node closeness-centrality, clustering and global network characteristics. Results: Death-related anxieties were highly frequent, each associated with at least moderate distress in 22%–55% of patients. Distress about 'Running out of time' was a central concern in the network. The network was organised into two areas: one about more practical fears concerning the process of dying and another about more psychosocial or existential concerns including relational problems, uncertainty about the future and missed opportunities. Both areas were yet closely connected by bridges which, for example, linked fear of suffering and a prolonged death to fear of burdening others. Conclusions: Patients with advanced cancer may have many interconnected death-related fears that can be patterned in individual ways. The bridging links between more practical and more psychosocial concerns emphasise that the alleviation of death anxiety may require interventions that integrate symptom management, advance care planning and psychological treatment approaches.